FISHING EXPERIMENTS WITH FRAME NETS IN HIRAKUD RESERVOIR , OORISSA - NAIDU, R M; GEORGE, V C (Fishery Technology, 2025)
Experiments conducted with frame nets of sizes 1.0 m, 1.25 m1.5 m, 1.75 m and 2.0 m in Hirakud Reservoir showed that the net with1.75 m frame gave the highest catches.